Cyclical electrical stimulation increases strength and improves activity after stroke: A systematic review - Nascimento L.R. (2014)
Question: Does electrical stimulation increase strength after stroke and are any benefits maintained beyond the intervention period or carried over to activity? Design: Systematic review with meta-analysis of randomised or controlled trials. Participants: Adults who have had a stroke. Intervention: Cyclical electrical stimulation applied in order to increase muscle strength. Outcome measures: Strength measures had to be representative of maximum voluntary contraction and were obtained as continuous measures of force or torque, or ordinal measures such as manual muscle tests. Activity was measured using direct measures of performance that produced continuous or ordinal data, or with scales that produced ordinal data. Results: Sixteen trials representing 17 relevant comparisons were included in this systematic review. Effect sizes were calculated as standardised mean differences because various muscles were studied and different outcome measures were used. Overall, electrical stimulation increased strength by a standardised mean difference (SMD) of 0.47 (95% CI 0.26 to 0.68) and this effect was maintained beyond the intervention period (SMD 0.33, 95% CI 0.07 to 0.60). Electrical stimulation also improved activity (SMD 0.30, 95% CI 0.05 to 0.56) and this effect was also maintained beyond the intervention period (SMD 0.38, 95% CI 0.09 to 0.66). Conclusion: Cyclical electrical stimulation increases strength and improves activity after stroke. These benefits were maintained beyond the intervention period with a small-to-moderate effect size. The sustained effect on activity suggests that the benefits were incorporated into daily life. Review registration: PROSPERO (CRD42013003895). [. Nascimento LR, Michaelsen SM, Ada L, Polese JC, Teixeira-Salmela LF (2014) Cyclical electrical stimulation increases strength and improves activity after stroke: a systematic review. Journal of Physiotherapy 60: 22-30]. © 2014 Australian Physiotherapy Association.